Hydrogel Transformed from Nanoparticles for Prevention of Tissue Injury and Treatment of Inflammatory Diseases. Issue 16 (14th March 2022) - Li, Zimeng; Li, Gang; Xu, Jiajia; Li, Chenwen; Han, Songling; Zhang, Chunfan; Wu, Peng; Lin, Yongyao; Wang, Chenping; Zhang, Jianxiang; Li, Xiaodong
Abstract: Functional hydrogels responsive to physiological and pathological signals have extensive biomedical applications owing to their multiple advanced attributes. Herein, engineering of functional hydrogels is reported via transformable nanoparticles in response to the physiologically and pathologically acidic microenvironment. These nanoparticles are assembled by a multivalent hydrophobic, pH‐responsive cyclodextrin host material and a multivalent hydrophilic guest macromolecule. Driven by protons, the pH‐responsive host–guest nanoparticles can be transformed into hydrogel, resulting from proton‐triggered hydrolysis of the host material, generation of a hydrophilic multivalent host compound, and simultaneously enhanced inclusion interactions between host and guest molecules. By in situ forming a hydrogel barrier, the orally delivered transformable nanoparticles protect mice from ethanol‐ or drug‐induced gastric injury. In addition, this type of nanoparticles can serve as responsive and transformable nanovehicles for therapeutic agents to achieve triggerable and sustained drug delivery, thereby effectively treating typical inflammatory diseases, including periodontitis and arthritis in rats. With combined advantages of nanoparticles and hydrogels, together with their good in vivo safety, the engineered transformable nanoparticles hold great promise in tissue injury protection and site‐specific/local delivery of molecular and cellular therapeutic agents. Abstract : Hydrogel‐transformable nanoparticles responsive to physiologically/pathologically acidic microenvironments are engineered by self‐assembly of a pH‐sensitive multivalent host material and a multivalent guest polymer. Driven by protons, the pH‐responsive host–guest nanoparticles can transform into hydrogel. The transformable nanoparticles protect mice from induced gastric injury by in situ forming a hydrogel barrier. These nanoparticles can serve as transformable nanovehicles for treating inflammatory diseases.